Human Bocavirus Capsid Messenger RNA Detection in Children With Pneumonia. (22nd July 2017) - Schlaberg, Robert; Ampofo, Krow; Tardif, Keith D; Stockmann, Chris; Simmon, Keith E; Hymas, Weston; Flygare, Steven; Kennedy, Brett; Blaschke, Anne; Eilbeck, Karen; Yandell, Mark; McCullers, Jon A; et al.
Summary: Human bocavirus messenger RNA detection in nasopharyngeal specimens from children with community-acquired pneumonia (CAP) but not in asymptomatic children undergoing elective outpatient surgery supports the pathogenic role for this virus in CAP and may be a more specific target for diagnostic testing. Abstract: Background: The role of human bocavirus (HBoV) in respiratory illness is uncertain. HBoV genomic DNA is frequently detected in both ill and healthy children. We hypothesized that spliced viral capsid messenger RNA (mRNA) produced during active replication might be a better marker for acute infection. Methods: As part of the Etiology of Pneumonia in the Community (EPIC) study, children aged <18 years who were hospitalized with community-acquired pneumonia (CAP) and children asymptomatic at the time of elective outpatient surgery (controls) were enrolled. Nasopharyngeal/oropharyngeal specimens were tested for HBoV mRNA and genomic DNA by quantitative polymerase chain reaction. Results: HBoV DNA was detected in 10.4% of 1295 patients with CAP and 7.5% of 721 controls (odds ratio [OR], 1.4 [95% confidence interval CI, 1.0–2.0]); HBoV mRNA was detected in 2.1% and 0.4%, respectively (OR, 5.1 [95% CI, 1.6–26]). When adjusted for age, enrollment month, and detection of other respiratory viruses, HBoV mRNA detection (adjusted OR, 7.6 [95% CI, 1.5–38.4]) but not DNA (adjusted OR, 1.2 [95% CI, .6–2.4]) was associated with CAP. Among children with no other pathogens detected, HBoV mRNA (OR, 9.6 [95% CI, 1.9–82]) was strongly associated with CAP. Conclusions: Detection of HBoV mRNA but not DNA was associated with CAP, supporting a pathogenic role for HBoV in CAP. HBoV mRNA could be a useful target for diagnostic testing.